2014
DOI: 10.18632/oncotarget.1815
|View full text |Cite
|
Sign up to set email alerts
|

C1GALT1 overexpression promotes the invasive behavior of colon cancer cells through modifying O-glycosylation of FGFR2

Abstract: Core 1 β1,3-galactosyltransferase (C1GALT1) transfers galactose (Gal) to N-acetylgalactosamine (GalNAc) to form Galβ1,3GalNAc (T antigen). Aberrant O-glycans, such as T antigen, are commonly found in colorectal cancer. However, the role of C1GALT1 in colorectal cancer remains unclear. Here we showed that C1GALT1 was frequently overexpressed in colorectal tumors and is associated with poor survival. C1GALT1 overexpression promoted cell survival, migration, invasion, and sphere formation as well as tumor growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 35 publications
(34 reference statements)
2
63
0
Order By: Relevance
“…Consistent with this possibility, a previous study reported that ALK3 and ActR-IIB are O-GalNAcylated by Xenopus Galntl-1 and that ActR-IIB glycosylation prevents its dimerization with BMPRI36. In addition, the O-GalNAcylation of FGFR2 by an unknown GALNT has been shown to trigger the activation of downstream signalling35. The biochemical mechanisms by which the GALNT14-stimulated O-GalNAcylation of FGFR1 activates the downstream cascade are currently under investigation.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Consistent with this possibility, a previous study reported that ALK3 and ActR-IIB are O-GalNAcylated by Xenopus Galntl-1 and that ActR-IIB glycosylation prevents its dimerization with BMPRI36. In addition, the O-GalNAcylation of FGFR2 by an unknown GALNT has been shown to trigger the activation of downstream signalling35. The biochemical mechanisms by which the GALNT14-stimulated O-GalNAcylation of FGFR1 activates the downstream cascade are currently under investigation.…”
Section: Discussionmentioning
confidence: 63%
“…The O-GalNAcylation of cell-surface receptors by GALNTs has been shown to regulate downstream signalling cascades203536. Since our data suggest that GALNT14 inhibits BMP signalling, we examined whether GALNT14 exerts this effect by the O-GalNAcylation of BMPRs.…”
Section: Resultsmentioning
confidence: 99%
“…Dysregulated expression of mucin-type O-glycans has evidently lead to aberrant cellular response, particularly in cancer cells [4, 31]. We recently reported that C1GALT1 is up-regulated in colorectal cancer [16] and hepatocellular carcinoma [15]. Up-regulation of C1GALT1 enhanced malignant phenotypes in colorectal cancer and hepatocellular carcinoma through FGFR2 and MET signaling pathways, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Knockout of C1GALT1 causes spontaneous colitis [12] and thrombocytopenia [13] in mice and modulates platelet cell surface glycoproteins involved in platelet synthesis and hematopoiesis [14]. We recently reported that C1GALT1 alters O-glycan structures on MET and enhances MET dimerization in hepatocellular carcinoma [15]; and C1GALT1 modifies O-glycans on FGFR2 and its downstream signaling involved in colorectal cancer malignant phenotypes [16]. Several studies reported that T antigens are overexpressed in breast cancer metastatic tumor cells and overexpression of T antigen regulates breast cancer malignant phenotypes [6, 1719].…”
Section: Introductionmentioning
confidence: 99%
“…Knockout of C1GALT1 causes spontaneous colitis [12] and thrombocytopenia [13] in mice and modulates platelet cell surface glycoproteins involved in platelet synthesis and hematopoiesis [14]. We recently reported that C1GALT1 alters O-glycan structures on MET and enhances MET dimerization in hepatocellular carcinoma [15]; and C1GALT1 modifies O-glycans on FGFR2 and its downstream signaling involved in colorectal cancer malignant phenotypes [16]. Several studies reported that T antigens are overexpressed in breast cancer metastatic tumor cells and overexpression of T antigen regulates breast cancer malignant phenotypes [6,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%